Speciation and conversion of carbon and nitrogen in young landfill leachate during anaerobic biological pretreatment. (1st April 2020) - Li, Runwei; Li, Liang; Zhang, Zhiming; Chen, Huan; McKenna, Amy M.; Chen, Gang; Tang, Youneng
Highlights: The anaerobic bioreactor removed 42% of fulvic acids. The anaerobic bioreactor removed 98% of recalcitrant dissolved organic nitrogen. The removed nitrogen correlated to compounds with low O:C and/or N:C ratios. The removed carbon correlated to compounds with low O:C and/or H:C ratios. Abstract: There is an increasing need for landfill leachate pretreatment prior to discharge to wastewater treatment plants due to increasingly stringent sewer discharge limits. Lab-scale tests have shown that the anaerobic biological processes can effectively remove chemical oxygen demand and dissolved organic carbon from landfill leachate. Our work expands the knowledge in anaerobic leachate pretreatment by systematically studying the conversion of carbon and nitrogen species, particularly their recalcitrant fractions in a submerged anaerobic biofilm reactor using real-world leachate from a typical young municipal solid waste landfill. After reaching steady state, the reactor removed 41.7% of the fulvic acids ( i.e., 1290 mg C/L). While compounds with a low degree of oxidation (O:C < 0.2) and compounds with a low degree of saturation (H:C < 1) were removed, compounds that were more oxidized (O:C > 0.2) and more saturated (H:C > 1) were produced. At steady state, 98% of recalcitrant dissolved organic nitrogen ( i.e., rDON = 222 mg N/L) was removed. Compared to the DON in the raw leachate, the produced DON in the pre-treated leachate were more oxidized (O:C > 0.35) and more bioavailable (N:C > 0.07). The submerged anaerobic biofilm reactor may be an efficient leachate pretreatment method if rDON removal is needed.